UNSPOKEN TRAUMA: INTERPRETING SILENCE AND OMISSION THROUGH A SOCIO-COGNITIVE DISCOURSE FRAMEWORK IN A LITTLE LIFE - Karisma Erikson Tarigan (International Journal of Multidisciplinary Research and Literature, 2026)
Silence and omission play a significant role in discourse, particularly in representing complex experiences such as trauma; however, they are often overlooked as meaningful linguistic elements. While previous studies have examined trauma in literary texts, limited research has analyzed how silence and omission are systematically realized at the clause level and interpreted through a socio-cognitive perspective. This study addresses that gap by investigating the linguistic realization and functions of silence and omission in Hanya Yanagihara’s A Little Life. This research employs a qualitative descriptive design with clause-level analysis as the unit of investigation. The data consist of 387 clauses selected through a systematic data reduction process from an initial dataset, focusing on expressions that reflect silence, omission, avoidance, and indirect discourse. The analysis applies a socio-cognitive discourse framework to interpret how these linguistic patterns relate to mental processes and social interaction. The findings show that silence and omission are realized through various forms, including explicit silence, vague or incomplete expressions, avoidance strategies, non-verbal communication, and minimal responses. The distribution of data indicates that cognitive and emotional processing is the most dominant pattern (39.8%), followed by silence and non-verbal expression (18.3%), avoidance and deflection (15.0%), omission and concealment (13.7%), and socio-discursive regulation (13.2%). These results demonstrate that silence and omission function as mechanisms for expressing unspoken trauma through cognitive limitation, emotional suppression, and socially regulated interaction. This study contributes to discourse analysis by demonstrating that meaning is constructed not only through explicit language but also through absence and indirect expression. It also highlights the relevance of a socio-cognitive approach in understanding how language, cognition, and social context interact in representing trauma.